Sri Lanka Electric Power Technology Assessment - World Bank (Washington, DC, 2014)
This study examines a broad selection of sustainable transport sector policy options from the standpoint of a common set of consistently defined attributes. Ideally, sustainable transport development should focus on the economic, environmental and social dimensions of sustainable development. However, in this volume, the first two aspects receive greater attention. The social dimension is examined mainly from the equity viewpoint, due to lack of time and data with regard to other key social indicators.